Platelet-Rich Plasma and its Use for Cicatricial and Non-Cicatricial Alopecias: A Narrative Review - Rubina Alves; Ramon Grimalt (Adis, Springer Healthcare, 2020)
Abstract The concept and description of platelet-rich plasma (PRP) started in the field of hematology and is being extensively used in other fields of medicine. Interest in the application of PRP has been increasing in dermatology, such as in tissue regeneration, wound healing, scar revision, skin-rejuvenating effects, and alopecia. PRP is an autologous blood product containing high concentrations of platelets in a small volume of plasma. Different preparations of PRP may lead to different volumes of PRP, platelet concentration, and presence or absence of leukocytes. PRP is being used as a new therapy for some types of non-cicatricial alopecia such as androgenetic alopecia (AGA) and alopecia areata (AA) and, recently, new insights refer to the possibility of action in the field of cicatricial alopecia, like lichen planopillaris (LPP) and frontal fibrosing alopecia (FFA). This article aims to identify the major indications for the application of PRP in the field of hair disorders, including non-cicatricial and cicatricial alopecia.